Chemotherapy for gestational trophoblastic neoplasia patients with a FIGO score of 12 or greater: A multistudy analysis. (July 2019) - Li, Jun; Yue, Huiran; Wang, Xingran; Chen, Ruifang; Lu, Xin
Abstract: Objective: To enable a comparison of reported chemotherapy regimens in gestational trophoblastic neoplasia (GTN) patients with a International Federation of Gynecology and Obstetrics (FIGO) score ≥12. Study design: Studies reporting cases of GTN with a FIGO score ≥12 were collected and screened for eligibility. A total of 17 studies encompassing 256 patients were included in final analysis. Results: In the first-line setting, etoposide-methotrexate-dactinomycin alternating with cyclophosphamide-vincristine (EMA/CO), etoposide-platinum alternating with EMA (EP/EMA), and floxuridine-dactinomycin-etoposide-vincristine (FAEV) were the three most commonly used regimens. The complete response (CR) rate was 55.2% for EMA/CO, 60.0% for EP/EMA, and 63.1% for FAEV. There was no significant difference in CR rate among EMA/CO, EP/EMA and FAEV in the first-line setting. While limited by low number, the CR rate was 66.67% for methotrexate-bleomycin -etoposide (MBE), and 25% for vincristine-dactinomycin-cyclophosphamide (VAC). Of the patients who failed initial therapy, EMA/CO, EP/EMA, and paclitaxel- cisplatin alternating with paclitaxel-etoposide (TP/TE) were the three most commonly used salvage regimens. The CR rate was 39.7% for EMA/CO, 35.0% for EP/EMA, and 11.8% for TP/TE. While limited by low number, MBE was used in 5 patients and yielded a 80% CR rate. Of the fatal cases, 21 (61.8%) patients had brain metastases, and 41.2% (14/34) of the deaths were early deaths. Conclusion: EMA/CO, EP/EMA, and FAEV yielded comparable CR rates in GTN patients with a FIGO score ≥12 in the first-line setting.